Analisa risiko pembangunan dermaga untuk pembangkit listrik terapung (Barge Mounted Power Plant/BMPP) di Kolaka, Sulawesi Tenggara - Yani Esbe; Savitri Citra Budi; Irawadi Prihaswan (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Electricity utilization in the provinces of South Sulawesi, Southeast and West Sulawesi is rapidly growing at a high rate. In Southeast Sulawesi Province, between the years of 2020 and 2024, it significantly grew by 12.66% per year. To meet with this high demand, for such a reason, PT Perusahaan Listrik Negara Indonesia Power/Electricity State Owned Company Info (PLN) ordered Nusantara II Barge Mounted Power Plant (BMPP) to PT PAL Surabaya and built a new jetty to mount the 60 MW plant in Wolo, Kolaka, Southeast Sulawesi. It is important to conduct risk management to ensure the success of the project by identifying and mitigating impact the risks that could be an obstacle smoothing delivery of the BMPP and the construction of its mounting dock. This study aims to analyze and manage risks for the construction of the BMPP Jetty. A risk analysis of the project was made to oversee what risks could interfere during the procurement stage, delivery the plant, implementation/construction stage up to the completion of the project. The research in this paper uses a descriptive qualitative approach and survey to examine the consequences of risks collected based on purposive sampling from Users, Contractors, Project Owners, and Project workers. The identified risks are then calculated and mitigated as necessary to control them. There were 47 risks identified, and after thorough analysis using the HIRADC method, 17 (36%) risks were low, 29 (62%) risks were moderate and 1 (2%) risk was high risk, which was related to the delivery of the BMPP itself. This research can help users, project owners, or other stakeholders in identifying, understanding, and responding to risks more effectively so that projects can be completed on time, without work accidents, but good quality, and within the planned budget. Good risk control and mitigation have made the project completed on time without accidents, delays, and with good quality delivered. The pattern of project implementation and management are be able to serve as reference to similar project in the future.